The life and work of General Andrew J. Goodpaster : best practices in national security affairs - Nelson, C. Richard (American warriors (Lexington, Ky.), 2016)
"This biography shows the importance of experienced soldier-scholars with high integrity on national security teams and provides the first systematic mining of the documents Goodpaster wrote on national security. Organized chronologically, it demonstrates how Goodpaster was able to adapt best practices to a constantly changing political, military, economic and technological environment. It also explains why he was so frequently selected as an insider in national security decision making. His life and work reveal how best to approach complex national security problems and the kind of collaborative leadership needed to get the job done. Still today, his method confirms General Scowcroft's view that Goodpaster is "too important to ignore."--Provided by publisher